Watch the Crowd: Bystander Responses, Trickle-Down Politics, and Xenophobic Mobilization - Robert Braun; Ruud Koopmans (Comparative Political Studies, 2014)
Social movement scholars have struggled with the question how abstract political opportunities affect activists without much knowledge of politics. We argue that the relationship between institutional opportunities and mobilization may take the form of trickle-down politics. In this view, activists are affected by political opportunities indirectly through the changes that political developments bring about in the immediate setting of protest. The political climate determines the distance between general public opinion and activists' view on society. The smaller this distance, the more likely it becomes that activists receive positive feedback, which results in further mobilization. We investigate how activists are influenced by bystander responses that are evoked by the wider political context. Statistical models indeed indicate that spatiotemporal fluctuations in political opportunities and public sentiments are translated into mobilization after activists receive feedback from bystanders. This suggests that bystander responses play a crucial role in linking political opportunities to mobilization.
Keywords: 330; ethnic violence; social movements; opportunity structures; structure-agency debates; Germany